Power and Geopolitics along the Mekong: The Laos–Vietnam Negotiation on the Xayaburi Dam. Issue 2 (August 2018) - Giovannini, Gabriele
This article is the first account of an overlooked aspect of the Xayaburi Dam, currently under construction in Laos in the mainstream of the Lower Mekong River; namely, the negotiations between Laos and Vietnam. Despite broad consensus among scholars and observers that Vietnam and Laos had diverging interests and preferences regarding the Xayaburi Dam, how Laos went ahead with the project despite Vietnam's explicit opposition to it has so far remained completely uncharted. This article aims to fill this knowledge gap by focusing on the state-to-state level of the Xayaburi Dam and addressing the factors that enabled Laos to pursue its interests prevailing over Vietnam despite the clear power asymmetry that shapes the bilateral relationship. The article concludes that geopolitical factors have limited Vietnam's leverage and its capacity to implement effective countermeasures to prevent Laos going ahead with the construction of the dam and have led to a positive outcome in relational power terms for Laos.